Pengaruh Pendapatan Kamar dan Biaya Komisi Penjualan Terhadap Average Room Rate Hotel di Daerah Denpasar - Budi Darma, Putu Sanjaya; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of room income and sales commission costs on the average room rate of hotels in the Denpasar area .The number of samples of this study were 80 hotels registered in the association hotel Denpasar. Data collection is done by non-participant observation method. Based on the results of the analysis it was found that room income and sales commission costs simultaneously had a significant effect on AAR. Room income partially has a significant effect on AAR. This shows that satisfying a room will provide a good average room rate. Sales commissions partially have a significant effect on AAR This shows that the sales commission from the room revenue generated given to travel agents will be better productivity for the average hotel rate hotel that is given. Keywords: Room income, sales commission costs, average room rate